Prevalência de anticorpos contra o vírus da hepatite A (HAV) em crianças de um a três anos de idade vacinadas contra o HAV com dose única - Brito, Wagner Izidoro de (2017)
Hepatitis A virus (HAV) causes an infection transmitted by fecal-oral route that occurs worldwide, especially in poor income countries. Brazil undergoes a period of transition from high endemicity to intermediate. Higher incidence rates take place in northernmost part of the country. In addition to basic sanitation, vaccination is one of the key measures to reduce this burden. HAV vaccines are commercially available since 1990’s. The inactivated virus vaccine, applied in two doses, was instituted in universal childhood vaccination programs in several countries, with proven effectiveness in reducing the incidence of the disease. The Brazilian Immunization Program (PNI) introduced the universal vaccination of children in 2014. Brazil adopted the schedule proposed in Argentina: a single dosis of inactivated virus vaccine in the second year of life. In order to estimate the HAV-antibody prevalence, after vaccination was performed a sectional study in Primavera do Leste, a county in Mato Grosso state, Central Brazil. The study allocated children from one month to less than two years after vaccination. Blood samples were collected from digital pulp by dried blood spots (DBS). The children’s responsible were invited to participate by information disseminated by health community agents. The main of study were explained to the responsible by the research team. 265 one- to three- years old children were included. 218 children tested positive for anti-HAV by DBS samples. Thirty-four out of 47 antiHAV negative children were retested by standard anti-HAV test from blood collected from antecubital vein. Eighteen tested positive and 16 remained anti-HAV negative. Among 252 anti-HAV positive by DBS children and 34 retested by venous blood, 50.8% were male. 236 (93.6%) out of 252 were anti-HAV positive. Among them, 92.4% were detected by DBS. Demographic and epidemiological variables were not associated to anti-HAV positivity by multivariate analysis, except having received other vaccine besides HAV vaccine on the same day (p=0,05). The sixteen children that anti-HAV was confirmed to be negative were revaccinated. The present study showed that the strategy adopted in Brazil generated high levels of anti-HAV positivity right after the vaccination. In addition, use DBS to test anti-HAV has proved to be useful to assess HAV vaccine efficacy in young children. Anyway, this method has less sensitivity to detect anti-HAV than the standard methodology with venous blood. This research demonstrated that children vaccinated with inactivated virus vaccine against hepatitis A, applied in only one dose, present high anti-HAV positivity. Follow-up studies of children's sections vaccinated with a single dose of the vaccine will be necessary to assess how long the antibody levels persists.